Searching full-text electronic versions of periodicals on technology and agriculture in Internet (Библиосфера)
Article features the search of electronic versions of technical and agricultural journals via search engines and e-catalogs, a comparative analysis of search capabilities in Google, MAIL.RU catalog, Scientific Electronic Library (SEL) eLIBRARY.RU, SPSL, sites of periodicals by Library.ru, CSAL, the NBU named after V. I. Vernadsky, the Belarusian Agricultural Library named after I. S. Lupinovich. Ite characterizes the navigational capabilities of directories and guides generated by the NLR and central libraries of the Russian Federation.